Researching the Reintegration of Formerly Abducted Children in Northern Uganda through Action Research: Experiences and Reflections - Angucia, Margaret; Zeelen, Jacques; De Jong, Gideon (Journal of Community & Applied Social Psychology, 2010)
This paper presents experiences and reflections on the use of a participatory research methodology under the difficult conditions of a war situation in northern Uganda. We draw from two complimentary approaches in action research to explain our methodology while doing research on the reintegration of formerly abducted children. First, the experience oriented approach, which emphasizes the need to articulate experience as a basis for learning and knowledge. Second, the exemplary participatory approach which highlights the importance of enhancing empowerment and the need to find solutions for social problems.We find these two approaches useful for doing action research in a conflict area because of their emphasis on experience and empowerment respectively. In our research, experience is important because of the children’s encounter with the Lord’s Resistance Army (LRA) rebels that both needs to be understood and justifies reintegration. On the otherhand, empowerment is important for our assumption that the children’s experience and encounter with the LRA has disempowering effects on them. We demonstrate the use of the approaches in our research by enhancing participation, balancing power relations and being aware of ethical issues while at the same time attempting to make the research valid inspite of the challenges.
Keywords: Reintegration; Formerly abducted children; Child soldiers; War affected children; Action research; Conflict situations; Community involvement; Ethics in research